Noise Level Status in Siddharthanagar Municipality, Rupandehi, Nepal - Bhattarai, Lakshmi Nath (Himalayan Physics, 2015)
Undesirable sound for human hearing is called as noise. It was measured at the selected locations of silent, residential and commercial zones of Siddharthanagar Municipality by using Dick Smith Digital Sound Level Meter Q 1362 for ‘A’ weighting in day time at 9:00 AM to 6:00 PM in the month of November and December 2012. The result shows that at each location the Leq noise levels are above than the noise level standard prescribed by Government of Nepal and WHO. Maximum Leq of 81.9 dB(A) was observed at the Bus park of commercial area and minimum 54.5 dB(A) was observed at Medical College area of silent zone. In other places, the Leq lie in the range 56.2 dB(A) to 81.9 dB(A). The study showed that the places lying along highways have high level of noise which is due to bad condition of roads, vehicles and unnecessary use of horns The Himalayan Physics Vol. 5, No. 5, Nov. 2014 Page: 69-74